Ultrasonic-assisted synthesis of CaCu3Ti4O12/reduced graphene oxide composites for enhanced photocatalytic degradation of pharmaceutical products: Ibuprofen and Ciprofloxacin - Ahmadipour M.; Ardani M.R.; Sarafbidabad M.; Missaoui N.; Satgunam M.; Singh R.; Kahri H.; Pal U.; Pang A.L.; Iqbal M.S.; Garg R.; Bhattacharya A. (Springer, 2025)
The objective of this research is to create a highly effective approach for eliminating pollutants from the environment through the process of photocatalytic degradation. The study centers around the production of composites consisting of CaCu3Ti4O12 (CCTO) and reduced graphene oxide (rGO) using an ultrasonic-assisted method, with a focus on their capacity to degrade ibuprofen (IBF) and ciprofloxacin (CIP) via photodegradation. The impact of rGO on the structure, morphology, and optical properties of CCTO was inspected using XRD, FTIR, Raman, FESEM, XPS, BET, and UV?Vis. Morphology characterization showed that rGO particles were dispersed within the CCTO matrix without any specific chemical interaction between CCTO and C in the rGO. The BET analysis revealed that with increasing the amount of rGO in the composite, the specific surface area significantly increased compared to the CCTO standalone. Besides, increasing rGO resulted in a reduction in the optical bandgap energy to around 2.09 eV, makes it highly promising photocatalyst for environmental applications. The photodegradation of IBF and CIP was monitored using visible light irradiation. The results revealed that both components were degraded above 97% after 60 min. The photocatalyst showed an excellent reusability performance with a slight decrease after five runs to 93% photodegradation efficiency. ? The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.